Patriarchal system of colonial import article in the Andes - Alvites Sosa, Lucía (2018)
Patriarchy was an import in the Andes, he came together with the colony as an axis of domination. And, although today it is a heavy own inheritance, there is also an ancestral memory of other possible orders gender. In this regard, we investigate the origins of gender relations in pre colonial Latin America, specifically in the Tahuantinsuyo, as accumulated synthetic expression of thousands of previous years of our prehispanic cultures.